Socio-Economic and Parental Attention toward Learning Achievement with Mediation of Motivation to Learn - Hutasuhut, Saidun; Wirawan, Indah Putri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
This study investigates the influence of parents' socio-economic conditions and attention to motivation to learn and learning achievement, moreover, also examine the mediation of motivation to learn on the influence of socio-economic conditions and parents' attention toward learning achievement. This study uses the ex-post-facto method. The data collection used in this study was questionnaires. The study population was eighth-grade students of junior high school in Medan, Indonesia, as many as 213 people and the samples taken were 138 people. The data analysis technique uses here as path analysis. The findings in the study are the socio-economic conditions and parents' attention directly, positively and significantly influence students' motivation to learn. Then the parents' socio-economic conditions, parents' attention, and motivation to learn have a positive and significant direct effect on learning achievement. Furthermore, motivation to learn is considered to mediate the influence of socio-economic conditions and parents' attention to social studies learning achievement. Parents' attention also mediates the influence of parents' socio-economic conditions on motivation to learn and learning achievement. Learning achievement is more accessible to achieve for families with adequately socio-economic conditions. Social studies learning achievements can be improved by increasing the attention of parents because it will increase motivation and further improve learning achievement.